Breast Reconstruction in Becker Nevus Syndrome - Alexis K. Schlosser, MD; Mohammed S. Rais, BS; Ruston J. Sanchez, MD (Plastic and Reconstructive Surgery, Global Open, 2025)
Summary:. Becker nevus syndrome is a rare cutaneous disorder characterized by the presence of a hyperpigmented patch of skin typically occurring on the upper trunk, often associated with hypertrichosis, and sometimes associated with musculoskeletal abnormalities ipsilateral to the nevus. Becker nevus syndrome can lead to breast hypoplasia. Unlike other forms of breast hypoplasia, treatment should begin before the completion of breast development. Due to the rarity of the disease, breast reconstruction in these patients has no gold-standard approach, and treatment is often delayed. Therefore, our case report highlighted the need for early treatment and provided options for reconstruction in this population. Our case reported a single surgeon approach to breast hypoplasia in Becker nevus syndrome. Consent was obtained for medical photography and research purposes. A 37-year-old woman with hypertension presented with concerns regarding drastic breast asymmetry. On examination, she was noted to have significant breast asymmetry with right-sided hypoplasia, left macromastia, and a patchy hyperpigmented lesion along the right chest wall. After a discussion of surgical options, a right breast augmentation and left breast reduction was performed. The patient had no postoperative complications. She was satisfied with her breast size and symmetry at her 6-month postoperative clinic follow-up. Becker nevus syndrome in women may be more frequent than previously described in the literature, as it often goes undiagnosed. Little literature exists on providing surgical options. This article demonstrated a single-stage reconstruction that provided satisfactory results and improvement in symmetry.